(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This article examines the dramaturgy of psychological suffering and mental illness in the plays of Sarah Kane, focusing on Blasted (1995), Crave (1998), and 4.48 Psychosis (1999). Kane’s work emerges as a radical theatrical intervention that subverts traditional representations of madness by embodying trauma through disjointed form, poetic language, and fractured subjectivity. Rather than depicting mental illness through character-driven realism, Kane destabilizes narrative coherence, abandons conventional stage directions, and experiments with voice and identity to immerse audiences in the experiential dimensions of psychic pain. Drawing on trauma theory (Caruth, 1996), psychoanalytic perspectives on abjection and subjectivity (Kristeva, 1982), and critiques of psychiatric discourse (Foucault, 1988), the article argues that Kane’s plays offer a politically charged aesthetics of pain. Her dramaturgy invites critical reflection on the ethics of representation and the theatrical potential for articulating the inarticulable. By situating Kane within both postdramatic theatre (Lehmann, 2006) and broader cultural narratives of mental health, the study highlights how her work continues to resonate within contemporary discourse on trauma, subjectivity, and the social stigmatization of psychological illness.